Wound Healing Property of Curcuminoids as a Microcapsule-Incorporated Cream - Lee Fung Ang; Yusrida Darwis; Rhun Yian Koh; Kenny Voon Gah Leong; Mei Yeng Yew; Lip Yee Por; Mun Fei Yam (MDPI AG, 2019)
Curcuminoids have been used for the management of burns and wound healing in traditional Chinese medicine practices but the wide application of curcuminoids as a healing agent for wounds has always been a known problem due to their poor solubility, bioavailability, colour staining properties, as well as due to their intense photosensitivity and the need for further formulation approaches to maximise their various properties in order for them to considerably contribute towards the wound healing process. In the present study, a complex coacervation microencapsulation was used to encapsulate curcuminoids using gelatin B and chitosan. This study also focused on studying and confirming the potential of curcuminoids in a microencapsulated form as a wound healing agent. The potential of curcuminoids for wound management was evaluated using an in vitro human keratinocyte cell (HaCaT) model and the in vivo heater-inflicted burn wound model, providing evidence that the antioxidant activities of both forms of curcuminoids, encapsulated or not, are higher than those of butylated hydroxyanisole and butylated hydroxytoluene in trolox equivalent antioxidant capacity (TEAC) and (2,2-diphenyl-1-picryl-hydrazyl-hydrate) (DPPH) studies. However, curcuminoids did not have much impact towards cell migration and proliferation in comparison with the negative control in the in vitro HaCaT study. The micoencapsulation formulation was shown to significantly influence wound healing in terms of increasing the wound contraction rate, hydroxyproline synthesis, and greater epithelialisation, which in turn provides strong justification for the incorporation of the microencapsulated formulation of curcuminoids as a topical treatment for burns and wound healing management as it has the potential to act as a crucial wound healing agent in healthcare settings.